Banana Market - Edward Evans; Fredy Ballen (EDIS)
The United States is the largest single-country importer of fresh bananas. With a per capita consumption of about 25 pounds, the banana market appears to be saturated, but consumption of organic bananas in the United States is increasing. Any expansion of the banana production in the United States should focus on the niche market for organic bananas and specialty varieties as Florida growers do. This 10-page fact sheet provides an overview of the world and US markets for fresh bananas, with special reference to the US market for organic bananas. Written by Edward Evans and Fredy Ballen, and published by the UF Department of Food and Resource Economics, February 2012.